Quid est veritas? Augustinus oor waarheid en leuen - en latere ontwikkelings 1 - Wyk, J. H. van (Hervormde teologiese studies, 2000)
Quid est veritas? Augustine on truth and lying - and the aftermath. In this article the author investigates the (very difficult) issue of truth and lying. What does it mean to speak the truth and when does a person tell a lie? The Augustinian as well as post-Augustinian views are enumerated and some of the main truth theories evaluated. In conclusion the author tries to make a final assessment and to open new ways of thinking the truth. Truth is a multidimensional category which should never be over-simplified.